Speaking Skill Development through the Implementation of Multimedia Projects (GIST – Education and Learning Research Journal, 2016)
The purpose of this study was to examine the way the implementation of podcasts, videos and PowerPoint projects fosters the speaking skill development in EFL sixth graders. In this action research, data were collected through an initial diagnosis and a final development test, a focus group interview, participant observation and students’ artifacts derived from podcast, video and PowerPoint projects. The data were then analyzed in a mixed method approach and results suggested that the majority of students became highly engaged in communicative situations, which allowed them to improve their limited language proficiency
Keywords: Speaking skill development; multimedia projects; Project work; high school students